2012
DOI: 10.1021/cb300208g
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Small-Molecule Antagonists of the Pseudomonas aeruginosa Transcriptional Regulator PqsR: Biophysically Guided Hit Discovery and Optimization

Abstract: The Gram-negative pathogen Pseudomonas aeruginosa produces an intercellular alkyl quinolone signaling molecule, the Pseudomonas quinolone signal. The pqs quorum sensing communication system that is characteristic for P. aeruginosa regulates the production of virulence factors. Therefore, we consider the pqs system a novel target to limit P. aeruginosa pathogenicity. Here, we present small molecules targeting a key player of the pqs system, PqsR. A rational design strategy in combination with surface plasmon re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 38 publications
0
74
0
3
Order By: Relevance
“…Although the potency of compound 11 was less than that of HHQ analogues 19 and 20, compound 11 has a lower molecular weight and is therefore more amenable to further optimization for use in vivo. This second report also helped define structural features of PqsR ligands that determine agonism versus antagonism (229), making rational design of potent PqsR antagonists more feasible moving forward.…”
Section: Inhibition Of Signal Detection Synthetic Signal Analogues Anmentioning
confidence: 95%
See 1 more Smart Citation
“…Although the potency of compound 11 was less than that of HHQ analogues 19 and 20, compound 11 has a lower molecular weight and is therefore more amenable to further optimization for use in vivo. This second report also helped define structural features of PqsR ligands that determine agonism versus antagonism (229), making rational design of potent PqsR antagonists more feasible moving forward.…”
Section: Inhibition Of Signal Detection Synthetic Signal Analogues Anmentioning
confidence: 95%
“…Surpris- ingly, however, elastase production and rhamnolipid production were not inhibited even at higher concentrations of the compound, but no explanation for these results was provided (127). In a follow-up report by the same group, rational design strategy and SPR biosensor analysis were used to identify additional PqsR binders (229). The -opioid receptor agonist (Ϯ)-trans-U50488, which was previously shown to activate quinolone signaling in P. aeruginosa (230), was used as a starting point for fragment-based design of novel inhibitors.…”
Section: Inhibition Of Signal Detection Synthetic Signal Analogues Anmentioning
confidence: 99%
“…However, both HHQ and PQS are coinducers of the virulence-associated LysR-type transcriptional regulator PqsR (41). The structural moieties that underpin the interaction between HHQ/PQS and PqsR remain to be fully characterized, although recent studies have reported diverse classes of PqsR antagonists (53)(54)(55) and implicated the hydrophobic pocket situated within the PqsR protein (56). Therefore, in order to assess whether the lead compounds could elicit a virulence response from P. aeruginosa, phenazine production and pqsA promoter activity (57) were monitored in a pqsA mutant where the capacity to produce native HHQ and PQS had been lost.…”
Section: Fig 3 Microscopic Analysis Reveals Altered Biofilm Structurementioning
confidence: 99%
“…8) were studied and interesting agonistic or antagonistic activities were observed, depending on the substitution pattern. [18] In Vibrio spp., a second quorum sensing system was discovered and termed autoinducer-2 (AI-2). This system is believed to allow interspecies communication.…”
Section: Ta Rgeting Quorum Sensingmentioning
confidence: 99%
“…Promising results, especially from interference with quorum sensing and adhesins, must now be further translated into early clinical phases to prevent the aforementioned scenarios of untreatable infections with Gram-negative bacteria. (17)(18)(19) and PapG (20,21), and P. aeruginosa LecA (23)(24)(25) and LecB (26)(27)(28)(29).…”
Section: Ta Rgeting Quorum Sensingmentioning
confidence: 99%